COMPARING THE ULCEROPROTECTIVE EFFECTS OF VERAPAMIL, RANITIDINE COMBINATION WITH OMEPRAZOLEON ASPIRIN INDUCED GASTROPATHY IN RABBITS - Muhammad Wasiullah Khan; Junaid Aslam; Ayesha Ellahi; Salma Bakhtiar (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the ulceroprotective effects of Verapamil on aspirin-induced gastropathy in rabbits.